Physics from natural philosophy to the enigma of dark matter - Rooney, Anne (How the world works, 2017)
"The laws of physics govern the action of everything, from galaxies to subatomic particles. From the ancient Greeks, who first suggested that matter might be made out of indivisible atoms, through the great explorations of Arab, then Renaissance and Enlightenment scientists, the story of physics has been written through trial and error, sheer persistence and intermittent flashes of sheer genius, despite many periods of persecution, hardship and danger. Author Anne Rooney follows this narrative from the earliest societies to the current day, discovering the entrancing appeal of the secrest that rule the universe. On the way from prehistory to the 21st century, we encounter Newton poking a needle into his own eye, Einstein paving the way for nuclear weapons, and the ultimate puzzle of dark matter."